Pollution by organic matter and autodepuration of water courses: impacts of this study in the production sector (Research, Society and Development, 2019)
The current organizational competitive landscape requires companies to make better use of their resources, as well as constantly optimizing the processes that permeate their activities. In addition, issues such as sustainability and environmental responsibility are increasingly present in the industry, becoming even more a tool for process improvement. Analyzing the production from this point of view, this article proposes a discussion about the applicability of studies on organic matter pollution and autodepuration of water courses, using mathematical knowledge, by the Streeter-Phelps model, for validation of the results and projection of the insertion of this study in the field of reuse of water by treatment plants, with the purpose of eliminating waste and optimizing production.